Pelatihan Pembuatan Gantungan Kunci dan PIN Bagi Siswa dan Siswi Madrasah Tsanawiyah Ma’arif NU Cijeruk Kabupaten Bogor dalam Mendukung Program Kewirausahaan - Tansah Rahmatullah (LPPM UNINUS, 2018)
MTS NU Ma'arif Cijeruk District Bogor is a private school which is most of the students studied come from families that are economically underprivileged. The problem will become more complicated, if the children as learners are not prepared and given life skills to have the know-how, skills, and independence to potential and opportunities in solving the problems of their own. Therefore, this community service is implemented to contribute to unravel the issue which was realized in the form of self-motivation training program execution as well as key chains and pins making for Learners MTS NU Ma'arif Cijeruk District Bogor. These activities are expected to help learners to become better prepared, independent and become a productive employee. The activities carried out in three stages, namely (1) the planning, (2) implementation, (3) the evaluation. The planning phase consists of activities to determine the location and types of activities, as well as the tools and materials used. Meanwhile the stages of implementation are in the form of, (1) material presentation, (2) product manufacturing of key chains and pins, (3) surveillance against the students who worked on the product in accordance with the directions and instructions. The last stage which is evaluation and reporting. After going through several phases, the learners can make the products according to the order and steps as well as the criteria that have been set to very good final result. In the end, the learners Mts NU Ma'arif Cijeruk District Bogor havebetter potential, skills, and productivity